In Vino Veritas: Klimatologische en socio-economische verklaringen voor de neergang van de Leuvense wijnteelt - Walschap, Lena (TSEG - The Low Countries Journal of Social and Economic History, 2020)
In Vino Veritas. Climatic and socioeconomic explanations for the decline of the wine production in Leuven. In the past, wine cultivation in Europe was much more widespread than it is today. However, around the sixteenth century, vineyards disappeared in many regions and wine cultivation was in decline. To explain this, convincing arguments have been made on the importance of both climatic and economic circumstances. By considering explanations from different viewpoints for the case of Leuven, this article explains why no consistent conclusion has been reached in the past. Climatic and economic factors were mutually reinforcing and cannot be considered separately. A combination of unpredictable harvests because of Little Ice Age weather types and small profits due to the unfavourable economic circumstances proved to be the perfect storm that caused the cultivation of grapevines in Leuven to no longer be worth pursuing.